Parallelizing Algorithm For Object Recognition Based On Edge Detection On Sunfire Cluster. - Osman, Mohd Azam; Sanudin, Maziani; Ibrahim, Muhammad Ismail (2007)
Object Recognition is one of the essential parts for image processing. It has become the major areas for the technologies like Biometrics, image recognition, authentication and accessibility of major security system